Universal Health Coverage dalam Membangun Ketahanan Kota Semarang - Indriyani, Nurul; Yuwono, Teguh (Journal of Politic and Government Studies, 2019)
Since the enactment of Regulation No.43 of 2017 concerning the implementation of health insurance namely Universal Health Coverage in collaboration with BPJS Kesehatan in Semarang City, society of Semarang City who do not have health insurance will be guaranteed by the City Government through a budget originating from the APBD so that with the presence of UHC the society can access health services for free as long as they want to be placed in Class III of Health Care Facilities.In its own implementation there are obstacles that hamper such as the lack of public knowledge about the existence of UHC. This study aims to analyze the implementation of UHC in the city of Semarang, especially in realizing the resilience of the city in Semarang and to describe the obstacles encountered in implementing UHC. The method used in this study is descriptive qualitative with the type of data used are primary data and secondary data and the data collection techniques used were interviews and documentation.. The results of the study show that with the enactment of the UHC, the health level of the city of Semarang has increased and disease outbreaks can be fought so that it contributes to realizing the resilience of the city. However, there are obstacles that are encountered where the lack of socialization that is done causes not all society know about UHC, besides that the community is considered to have the presumption that by registering UHC, the arrears with the BPJS Health does not need to be paid. Suggestions from this research are that it is better for the Semarang City Health Office as the executor to consistently intensify UHC socialization until the smallest government scope also emphasizes understanding of regulations related to delinquency fees with BPJS Health, and recommendations to consider the impact of the ever increasing number of UHC participants.